Effect of bone sialoprotein coated three‐dimensional printed calcium phosphate scaffolds on primary human osteoblasts. Issue 7 (9th January 2018) - Klein, Anja; Baranowski, Andreas; Ritz, Ulrike; Götz, Hermann; Heinemann, Sascha; Mattyasovszky, Stefan; Rommens, Pol M.; Hofmann, Alexander
Abstract: The combination of the two techniques of rapid prototyping 3D‐plotting and bioactive surface functionalization is presented, with emphasis on the in vitro effect of Bone Sialoprotein (BSP) on primary human osteoblasts (hOBs). Our primary objective was to demonstrate the BSP influence on the expression of distinctive osteoblast markers in hOBs. Secondary objectives included examinations of the scaffolds' surface and the stability of BSP‐coating as well as investigations of cell viability and proliferation. 3D‐plotted calcium phosphate cement (CPC) scaffolds were coated with BSP via physisorption. hOBs were seeded on the coated scaffolds, followed by cell viability measurements, gene expression analysis and visualization. Physisorption is an effective method for BSP‐coating. Coating with higher BSP concentrations leads to enhanced BSP release. Two BSP concentrations (50 and 200 μg/mL) were examined in this study. The lower BSP concentration (50 µg/mL) decreased ALP and SPARC expression, whereas the higher BSP concentration (200 μg/mL) did not change gene marker expression. Enhanced cell viability was observed on BSP‐coated scaffolds on day 3. hOBs developed a polygonal shape and connected in an intercellular network under BSP influence. Quantitative cell morphology analyses demonstrated for BSP‐coated CPCs an enhanced cell area and reduced circularity. The strength of the above‐mentioned effects of BSP‐coated scaffolds in vivo is unknown, and future work is focusing on bone ingrowth and vascularization in vivo . © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 106B: 2565–2575, 2018.